One-year outcome using cyanoacrylate glue to ablate truncal vein incompetence: A Singapore VenaSeal™ real-world post-market evaluation study (ASVS). (September 2021) - Tang, Tjun Y; Yap, Charyl JQ; Soon, Shereen XY; Chan, Sze L; Choke, Edward TC; Chong, Tze T
Objective: We present 12 months efficacy data from A Singapore VenaSeal™ real-world post-market evaluation Study (ASVS), a prospective single-arm Asian population registry aimed to evaluate cyanoacrylate glue (CAG) closure of refluxing truncal veins. Methods: Duplex ultrasound was used to assess truncal vein closure. The revised Venous Clinical Severity Score (rVCSS) and three quality of life (QoL) questionnaires were completed to assess improvement in venous disease symptoms. Results: 90/100 (90%) patients (136 legs; 140 truncal veins) completed evaluation at 6- and 12 months. The truncal closure rates at 6 and 12 months were 139/140 (99.3%) and 137/140 (97.9%), respectively. rVCSS and QoL questionnaires scores were sustained from the 3 to 12 months visits, although there were no futher significant improvement. No serious adverse events were reported between 3 and 12 months. Conclusions: CAG remains a safe and efficacious venous ablative technology at 12 months and is associated with a high rate of target vein occlusion and sustained QoL improvement.